2005
DOI: 10.1097/01.don.0000164131.46519.d5
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Model to Investigate Filling of Lateral Canals

Abstract: Aims of this work were to examine lateral canals in extracted teeth, to propose a new technique to produce artificial lateral canals, and to compare two obturation techniques. Cleared roots were examined to record measure and shape of lateral canals. Artificial lateral canals were prepared on human demineralized teeth before final clearing. Specimens were divided in two groups: canals of group 1 were filled with Schilder's technique, canals of group 2 were filled with vertical compaction with apical backfillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 31 publications
3
72
2
5
Order By: Relevance
“…10 Such small diameters, together with their location within the root canal system, may affect the filling of lateral canals. In this study, #8 and #10 K-files were used to create the simulated lateral canals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Such small diameters, together with their location within the root canal system, may affect the filling of lateral canals. In this study, #8 and #10 K-files were used to create the simulated lateral canals.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, #8 and #10 K-files were used to create the simulated lateral canals. Venturi et al 10 and Venturi 23 observed that natural apical ramifications were often left incompletely filled after warm vertical compaction. However, the technique used in this study proved safer, by promoting less extrusion of filling material than the Termafil technique.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations